16 participants of AEF2025 arrived in Malaysia for the UMPSA Mobility Program - Nadira Hana, Abd Hamid (UMPSA, 2025)
GAMBANG, 19 February 2025 - A total of 16 international participants from Indonesia, Vietnam, the Philippines, Cambodia and Thailand have safely arrived in Malaysia to participate in the ASEAN Student Mobility Program in conjunction with the ASEAN Universities Exhibition and Forum 2025 (AEF2025).